Physiotherapeutic treatment for temporomandibular disorders (TMD) - Débora Bevilaqua Grossi; Thais Cristina Chaves (Universidade Estadual de Campinas, 2015)
To a correct approach for TMD patient the physiotherapist must perform a diagnostic and anamnesis evaluation to make an effective therapeutic intervention. Literature presents some schemes, anamnesis indexes and standardized and validated questionnaires to evaluate TMD. Another important aspect is the biomechanical evaluation of the cervical spine alterations in TMD patients, due to the evidences of symptoms and biomechanical associations between cervical and masticatory systems. Manual therapy, therapeutical resources (like as ultra-sound, TENS) and postural re-education must be applied in a physical therapy treatment for TMD patients, but an appropriate intervention should be related not only to symptoms relief, but look for TMD´s etiology. In view of such considerations one of the most important approachs for TMD physical therapy treatment must be the modification of craniocervical biomechanics and its effects to posture as an etiologic or perpetuating TMD factor